The Economic and Social Effects of the COVID-19 Epidemic in the European Union over the Past Year, Especially in Hungary - Béresné, Bernadett; Maklári, Eszter (International Journal of Engineering and Management Sciences, 2021)
The apparence of the COVID-19 pandemic at the beginning of 2020 affected all countries in the world, entailing major changes in everyday life. In our study – in a one year perspective – we summerize the socio-economic effects of the COVID-19 pandemic on various economic sectors and their consequences for the European Union and Hungary. As a result of the pandemic restrictions the role of some sectors were decreasing considerably, while on the other hand the other sectors emerged and underwent a significant improvement. The growing trend of working from home, as well as the decline of the tourism, the catering service and the entertainment industry has led to a change in the behavior of the population. .    Changes during the pandemic period led to an increase in wealth inequalities.Changes  during the pandemic period led to anincreas  in economic inequality. The transformation of consumers’ values and income situation is having an huge impact on all sectors of the national economy. When reflecting upon the current situation, the following questions arise: When will the declining businesses be able to recover? Will they be able to achieve their pre-pandemic profit level, and if yes, how long will it take them?